2009
DOI: 10.1080/03014220909510137
|View full text |Cite
|
Sign up to set email alerts
|

First records of mermithid nematodes (Nematoda: Mermithidae) parasitising stick insects (Insecta: Phasmatodea)

Abstract: Hitherto the occurrence of mermithid nematodes (Nematoda: Mermithidae) parasitising stick insects has not been reported. Six mermithids were collected after emerging from specimens of New Zealand stick insects field collected and held in captivity. The mermithid nematodes are recorded from the stick insect genera Clitarchus Stål, Acanthoxyla Uvarov, Asteliaphasma Jewell & Brock and Tectarchus Salmon. Small subunit RNA (18S) sequence was obtained from one of the mermithid specimens. Phylogenetic analysis of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…The maximum‐likelihood phylogeny confirmed that the Timema endoparasitic nematodes are indeed closely related to species from the family Mermithidae of Nematoda (Clade I; Fig. A), and are closely related to the single mermithid ever collected from another stick insect ( Clitarchus ; Yeates and Buckley ; Fig. S1).…”
Section: Resultsmentioning
confidence: 57%
See 2 more Smart Citations
“…The maximum‐likelihood phylogeny confirmed that the Timema endoparasitic nematodes are indeed closely related to species from the family Mermithidae of Nematoda (Clade I; Fig. A), and are closely related to the single mermithid ever collected from another stick insect ( Clitarchus ; Yeates and Buckley ; Fig. S1).…”
Section: Resultsmentioning
confidence: 57%
“…In this study we identified a new group of endoparasitic nematodes, infecting at least nine species of Timema stick insects throughout California, as relatives of mermithid nematodes. This is only the second report of mermithid (or mermithid‐like) nematodes infecting stick insects, after Yeates and Buckley () found a mermithid nematode infecting a Clitarchus stick insect in New Zealand. We found that this mermithid is closely related to Timema endoparasites, suggesting few or perhaps even only a single colonization of phasmatodean hosts by mermithids.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The species has been reported from New Zealand only in passing, with MacFarlane (2011) and Thomas (1989) each offering personal observations that M. subnigrescens is common in earwigs in Canterbury; M. subnigrescens was synonymized with M. nigrescens by Nickle (1972). Other reports of mermithid genera from New Zealand include unidentified mermithid species in Ephemeroptera, Coleoptera, Phasmatodea and Orthoptera (Barker et al, 1989;Ward, 1998;Williams et al, 2001;Bell et al, 2005;Yeates & Buckley, 2009), Agamomermis sp. in midges (Craig, 1963), Aranimermis giganteus Poinar & Early, 1990 in mygalomorph spiders (Poinar & Early, 1990), Thaumamermis zealandica Poinar, Latham & Poulin, 2002 in supralittoral amphipods (Poinar et al, 2002), Psammomermis canterburiensis Poinar & Jackson, 1992 in scarabid beetle larvae (Hoy, 1952;Poinar & Jackson, 1992), and Austromermis namis Poinar, 1990 and Blepharomermis craigi Poinar, 1990 in blackfly and midge larvae (Poinar, 1990).…”
Section: Introductionmentioning
confidence: 96%
“…Although the species of mermithid was not identified, it is believed the same species attacked various species of collected. Yeates and Buckley [61] also describe records of mermithid nematodes attacking phasmids. Table 3 provides an overview of potential biological control agents.…”
Section: Potential For Biological Controlmentioning
confidence: 99%